The philosophies of science in developing nursing science - Ei Wah Phyu Thet; Amar Akbar (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
During the successive wave of globalization, nurses emphasized the requirement of specialized knowledge to improve the nursing as a profession and to make the transition from vocation to profession. The science of nursing is a foundation of knowing for nurses. Also there has a shift of nursing metaparadigm based on Kuhn’s philosophy of science. It was assumed that Philosophies are theoretical works that included one or more of the metaparadigm concepts. Philosophy provide us broad general view of what is science and human science, evolution of science, function of scientific theory, scientific methodologies, different philosophical approaches, significant philosophical shift in different eras and it would be helpful for the development of nursing as a discipline from adhering to the knowledge that we learnt in this paper.